Executive Committee Minutes 2017-05-11 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 4/28/17 approved. Chair Report. President Report. Revision to the Acting Concentration in Theater Arts and Dance referred back to EPC. Provost Report. Statewide Senator Report. Shared governance discussion prompted by CSUSB no confidence vote. Vice President of Administration and Finance Report. APARC Report. Feedback on electronic agendas and using iPads. Senate agenda approved. Associated Students report. EPC Report. Good of the Order.